2022
DOI: 10.34133/2022/9823784
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Stem Cell Recruitment and Osteoinduction via Bioadhesive Molecular Mimics to Improve Osteoporotic Bone-Implant Integration

Abstract: For patients with osteoporosis, the therapeutic outcomes of osteoimplants are substantially affected by the impaired proliferation, migration, and osteogenic differentiation abilities of bone marrow mesenchymal stem cells (BMSCs). To improve bone-implant integration in osteoporotic condition, here we reported a one-step biomimetic surface strategy to introduce BMSC recruiting and osteoinductive abilities onto metallic osteoimplants. In our design, the bioadhesive molecular peptide mimic inspired by mussel foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Compared to the antagonist or antibody of P‐selectin, PBP afforded unique advantages, including high‐throughput yields at a low cost benefiting from the contribution of the solid phase peptide synthesis technique and ease of conjugation or modification as required due to the relatively simplistic and well‐defined chemical structure of polypeptides. [ 10 ] Additionally, it has been proven that PBP has a remarkable P‐selectin binding specificity with high affinity, which provides sufficient strength for anchoring PBP‐EVs on the surface of injured ECs under the wall shear of hemodynamic flow. [ 10c ] Therefore, we rationalized that PBP not only enhanced the selective specificity of PBP‐EVs but also provided spatiotemporal convenience for PBP‐EVs to access into and penetrate the injured endothelial layer in injured kidneys, which demonstrated that PBP is a superior targeting ligand for EC‐targeted renal theranostics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the antagonist or antibody of P‐selectin, PBP afforded unique advantages, including high‐throughput yields at a low cost benefiting from the contribution of the solid phase peptide synthesis technique and ease of conjugation or modification as required due to the relatively simplistic and well‐defined chemical structure of polypeptides. [ 10 ] Additionally, it has been proven that PBP has a remarkable P‐selectin binding specificity with high affinity, which provides sufficient strength for anchoring PBP‐EVs on the surface of injured ECs under the wall shear of hemodynamic flow. [ 10c ] Therefore, we rationalized that PBP not only enhanced the selective specificity of PBP‐EVs but also provided spatiotemporal convenience for PBP‐EVs to access into and penetrate the injured endothelial layer in injured kidneys, which demonstrated that PBP is a superior targeting ligand for EC‐targeted renal theranostics.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Additionally, it has been proven that PBP has a remarkable P‐selectin binding specificity with high affinity, which provides sufficient strength for anchoring PBP‐EVs on the surface of injured ECs under the wall shear of hemodynamic flow. [ 10c ] Therefore, we rationalized that PBP not only enhanced the selective specificity of PBP‐EVs but also provided spatiotemporal convenience for PBP‐EVs to access into and penetrate the injured endothelial layer in injured kidneys, which demonstrated that PBP is a superior targeting ligand for EC‐targeted renal theranostics.…”
Section: Discussionmentioning
confidence: 99%
“…This multifunctional binding ability makes polyphenol species an ideal “bridge” molecule between inorganic and organic phases. Polyphenols inspired by mussels have been used to modify or coat inorganic and metal surfaces to enhance HAP crystallization, biomineralization, bone regeneration, , and cell adhesion. , At the same time, there are many similarities in environment between mussels and human oral environment, such as saline conditions, dynamic changes in fluid flow, pH, and temperature, and exposure to microorganisms and enzymes, which cause mussel-inspired solutions to be considered for a variety of properties widely used in dental materials. For example, deposited tannin–Fe 3+ complexes adsorbed calcium and phosphate ions in artificial saliva to induce the remineralization of HAP crystals .…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis (OP) is a systemic bone disease characterized by reduced bone mass, damaged bone microstructure, and increased bone fragility, leading to a high risk of fractures. , The disease is more common in postmenopausal women and the elderly population, and with the population aging, the incidence of OP continues to rise, bringing serious burdens to society and families. , Excessive activity of osteoclasts causing increased bone resorption is an important pathological mechanism of OP . Therefore, osteoclast inhibitors (such as bisphosphonates and calcitonin) are commonly used in clinical practice to treat OP and have achieved certain effects .…”
Section: Introductionmentioning
confidence: 99%